2002
DOI: 10.1123/jsr.11.4.252
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Isokinetic Muscle Strength of the Lower Extremity in Recreational Athletes with Anterior Cruciate Ligament Reconstruction

Abstract: Objective:To investigate changes in muscle strength in the lower extremity after ACL reconstruction.Design:Prospective case series.Dependent Variables:Isokinetic muscle strength measured in 6 movements (hip extension/flexion, hip adduction/abduction, knee extension/flexion) and circumference of the thigh/calf.Setting:Clinic and home.Patients:44 (24 men, 20 women) between the ages of 16 and 47 years with an ACL rupture. All underwent reconstruction via a semitendinosus autograft.Main Outcome Measures:The peak t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Upon comparison of our study results with those obtained by other authors, we noted that Urabe et al [19] did not obtain equalization of extensor muscle strength of the involved knees even after 12 months of rehabilitation, and at that time they reported a strength deficiency ranging from 8% to 10% in the involved legs. Such differences in time (delay) of muscle strength regain might have been due to the physiotherapeutic program.…”
Section: Discussionsupporting
confidence: 70%
“…Upon comparison of our study results with those obtained by other authors, we noted that Urabe et al [19] did not obtain equalization of extensor muscle strength of the involved knees even after 12 months of rehabilitation, and at that time they reported a strength deficiency ranging from 8% to 10% in the involved legs. Such differences in time (delay) of muscle strength regain might have been due to the physiotherapeutic program.…”
Section: Discussionsupporting
confidence: 70%
“…Seven were classified as good,43 45–47 53 55 66 26 as fair3 5–9 21 23 37–39 41 42 44 48–50 52 54 56 60–67 and 6 as poor 29 40 51 57–59. Thirty studies did not include all important adverse events that could have an effect on the intervention reported (criterion 8),5–7 9 21 23 29 38–40 42–52 54 56 57 59 60 63 64–67 23 studies did not adequately describe the source population and how they were recruited (criterion 11 and 12),3 5 6 8 21 37–40 42 44 48–52 54 57–60 64 65 24 studies did not describe if the source population was recruited in the same time period (criterion 22),3 8 9 23 29 37–42 44 48–52 54–58 63 64 66 and 29 studies did not report sample size calculation (criterion 27) 3 6–8 21 23 29 38–44 49–53 56–61 63–67. Other criterion, such as criterion 22 and 23, were not commonly fulfilled due to most studies not being randomised, while criterion 14 and 15 were not commonly reported due to lack of blinding.…”
Section: Resultsmentioning
confidence: 99%
“…Mode of contraction and angular velocity were reported in all the studies reviewed, but not all studies reported all aspects of their protocols. Of the 39 studies, 11 (28%) did not report number of repetitions,7 9 39 43 45 46 52 54 58 61 66 25 (64%) did not report range of motion,3 6–9 29 38 39 41 43 47–51 54 55 57 58 60 61 63 64–66 and 29 (74%) studies did not report if gravity correction was used 3 6 7 9 21 29 37 38–45 47 49 50 53–55 57 58 60 61 64–67…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations